Interactions between residues in staphylococcal alpha-hemolysin revealed by reversion mutagenesis. - Panchal, R; Bayley, H (1995)
alpha-Hemolysin (alpha HL), a pore-forming polypeptide of 293 amino acids, is secreted by Staphylococcus aureus as a water-soluble monomer. Residues that play key roles in the formation of functional heptameric pores on rabbit red blood cells (rRBC) have been identified previously by site-directed mutagenesis. alpha HL-H35N, in which the histidine at position 35 of the wild-type sequence is replaced with asparagine, is nonlytic and is arrested in assembly as a heptameric prepore. In this study, second-site revertants of H35N that have the ability to lyse rRBC were generated by error-prone PCR under conditions designed to produce single base changes. The analysis of 22 revertants revealed new codons clustered predominantly in three distinct regions of the H35N gene. One cluster includes amino acids 107-111 (four revertants) and another residues 144-155 (five revertants). These two clusters flank the central glycine-rich loop of alpha HL, which previously has been implicated in formation of the transmembrane channel, and encompass residues Lys-110 and Asp-152 that, like His-35, are crucial for lytic activity. The third cluster lies in the region spanning amino acids 217-228 (eight revertants), a region previously unexplored by mutagenesis. Single revertants were found at amino acid positions 84 and 169. When compared with H35N, the heptameric prepores formed by the revertants underwent more rapid conversion to fully assembled pores, as determined by conformational analysis by limited proteolysis. The rate of conversion to the fully assembled pore was strongly correlated with hemolytic activity. Previous work has suggested that the N terminus of alpha HL and the central loop cooperate in the final step of assembly. The present study suggests that the key N-terminal residue His-35 operates in conjunction with residues flanking the loop and C-terminal residues in the region 217-228. Hence, reversion mutagenesis extends the linear analysis that has been provided by direct point mutagenesis.